Submicrosecond atmospheric electric discharge from the non-uniform electrode (tip) towards the plane electrode - Kozhevnikov, Vasily Y.; Kozyrev, Andrey V.; Kokovin, Aleksandr O.; Igumnov, Vladislav S. (Vojnotehnički glasnik / Military Technical Courier, 2019)
This paper deals with the results of a numerical simulation of the fast atmospheric pressure discharge in a strongly non-uniform configuration of a tip-to-plane diode filled with a nitrogen and oxygen mixture. The simulation is based on the advanced hydrodynamic plasma discharge accounting also gas photoionization. It was shown that, in the absence of photoionization, discharge develops similarly to the case with photoionization, except the case of reversed voltage polarity. The theoretical results correspond to the existing experimental data for the spatial discharge structure and the current/voltage discharge characteristics.